A Survey of Neonatal Clinicians' Use, Needs, and Preferences for Kangaroo Care Devices. (June 2021) - Weber, Ashley; Jackson, Yamile
Abstract : Background: Decades of research supports the benefits of kangaroo care (KC) for the parent and newborn. Supportive KC devices may be an important tool clinicians can use to assist parents with KC. In recent years, there has been a rise in the availability of KC devices. However, the use, needs, and preferences for these supportive devices by neonatal clinicians have not been documented. Purpose: To survey clinicians' use, needs, and preferences of KC supportive devices, and examine whether differences exist based on clinician and organizational characteristics. Methods: A cross-sectional, online survey was sent through neonatal organization Web sites, conferences, and social media. Results: Many clinicians (n = 68, 43%; N = 158) facilitated KC with a supportive device, with 81% of devices provided by the clinician's employer. The most important "Must Have" feature of a KC device was "Safety: Reduces patient falls if caregiver sleeps or needs to use hands" (84% of respondents) followed by washability (82%), and "immediate, effective access to the baby" (78%). Clinicians' responses did not differ based on hospital setting, type of unit, KC experience, or experience using a KC device. Implications for Practice: To support safe use of KC devices in neonatal intensive care unit (NICU) clinical care, a device must hold the proper KC position consistently, allow immediate access to the infant, and hold the infant in place without the parent's hands to prevent falls. Training is needed to ensure safe device use. Implications for Research: Future research should evaluate the safety, efficacy, and cost-effectiveness of these devices.